Selection of succulent species to be used on green roofs according to phytogeographic regions: Türkiye example - Aksoy, Onur; Erken, Kamil (Ege Universitesi, 2024)
The objective of this study was to determine the succulent plant species that can be used on green roofs to be recommended for 3 phytogeographic regions in Türkiye. Three phytogeographic regions in Türkiye and the succulent taxa found in the natural flora of these regions were chosen as the study material. In the study, firstly, literature search was conducted. Then, family, endemism, hairiness, climate, altitude and habitat status of succulent species obtained from the literature were determined. In line with the information obtained in the last stage, taxa that can be recommended for green roofs in 3 different phytogeographic regions are listed. As a result of the study, it was determined that Saxifraga spp. and Sempervivum spp. in cool climates, Umbilicus spp. and Rosularia spp hot climates that the genera are the genera with the highest number of taxa. Also, ranked in both cool and warm climates, Sedum spp. and Rosularia spp. first in terms of the species richness of its genera The findings of this study are of importance in terms of helping the selection of the right succulent species that can be used on green roofs for countries located in similar phytogeographic regions around the world. © 2024 Ege Universitesi. All rights reserved.
Keywords: Cool climate succulent species; green roof; phytogeography; succulent plants; warm climate succulent species